Incidence of types of hypospadias in and around Tumkur district, Karnataka, India: an anatomical classification - N. M., Suresh; Kattepura, Subramanya; Yathindra, N.; Hussain Afroze, Khizer (International Journal of Research in Medical Sciences, 2018)
Background: Hypospadias is the second most common congenital anomaly in children. It is characterized by the abnormal ventral opening of the urethral meatus. Abnormal urethral opening may be located on the penile shaft, scrotum or perineum respectively. This article mainly deals with the embryology, etiology, anatomy and incidence of different types of hypospadias in Tumakuru rural district. Methods: This study was interdepartmental and prospective, consisting of 80 cases conducted at department of pediatric surgery and Anatomy and the period of study was from April 2013 to March 2017. The hypospadias have been classified into 1) Proximal hypospadias 2) Midshaft hypospadias, 3) Distal Hypospadias according to the location of external urethral opening. Results: Out of the 80 cases, distal hypospadias is the most common incidence followed by midshaft and proximal hypospadias. Conclusions: The condition is repairable in the vast majority of cases, leaving a functional and normal looking penis. Early diagnosis and surgical intervention, hypospadias and chordee repair procedures are highly successful and can avoid the emotional distress.